Community health worker training to reduce mental health and substance use stigma towards patients who have disengaged from HIV/TB care in South Africa: protocol for a stepped wedge hybrid type II pilot implementation trial - Myers, Bronwyn; Regenauer, K.S.; Rose, A.; Johnson, K.; Ndamase, S.; Ciya, N.; Brown, I.; Joska, J.; Bassett, I.V.; Belus, J.M.; Ma, T.; Sibeko, G.; et al. (2024)
Background: South Africa has deployed community health workers (CHWs) to support individuals to enter and stay in HIV/TB care. Although CHWs routinely encounter patients with mental health (particularly depression) and substance use (SU) conditions that impact their engagement in HIV/TB care, CHWs are rarely trained in how to work with these patients. This contributes to mental health and SU stigma among CHWs, a known barrier to patient engagement in care. Mental health and SU training interventions could reduce CHW stigma and potentially improve patient engagement in care, but evidence of the feasibility, acceptability, and preliminary effectiveness of these interventions is scarce. Therefore, we designed a hybrid type 2 effectiveness-implementation pilot trial to evaluate the implementation and preliminary effectiveness of a CHW training intervention for reducing depression and SU stigma in the Western Cape, South Africa. Methods: This stepped wedge pilot trial will engage CHWs from six primary care clinics offering HIV/TB care. Clinics will be block randomized into three-step cohorts that receive the intervention at varying time points. The Siyakhana intervention involves 3 days of training in depression and SU focused on psychoeducation, evidence-based skills for working with patients, and self-care strategies for promoting CHW wellness. The implementation strategy involves social contact with people with lived experience of depression/SU during training (via patient videos and a peer trainer) and clinical supervision to support CHWs to practice new skills. Both implementation outcomes (acceptability, feasibility, fidelity) and preliminary effectiveness of the intervention on CHW stigma will be assessed using mixed methods at 3- and 6-month follow-up assessments. Discussion: This trial will advance knowledge of the feasibility, acceptability, and preliminary effectiveness of a CHW training for reducing depression and SU stigma towards patients with HIV and/or TB. Study findings will inform a larger implementation trial to evaluate the longer-term implementation and effectiveness of this intervention for reducing CHW stigma towards patients with depression and SU and improving patient engagement in HIV/TB care. Trial registration: ClinicalTrials.gov NCT05282173. Registered on 7 March 2022.